2012
DOI: 10.1063/1.4752654
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of the decomposition of new imidazole based energetic materials: Model systems

Abstract: Decomposition of three imidazole based model energetic systems (2-nitroimidazole, 4-nitroimidazole, and 1-methyl-5-nitroimidazole) is investigated both experimentally and theoretically. The initial decomposition mechanism for these three nitroimidazoles is explored with nanosecond energy resolved spectroscopy, and quantum chemical theory at the complete active space self-consistent field (CASSCF) level. The NO molecule is observed as an initial decomposition product from these three nitroimidazoles subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 59 publications
4
71
0
Order By: Relevance
“…26 It was found that in both molecules NO • is formed as an initial product, irrespective of the excitation wavelength. Thereby NO • is generated with a rotationally cold (50 K) and vibrationally warm (800 K) distribution, independent of the excitation wavelength.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…26 It was found that in both molecules NO • is formed as an initial product, irrespective of the excitation wavelength. Thereby NO • is generated with a rotationally cold (50 K) and vibrationally warm (800 K) distribution, independent of the excitation wavelength.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…9 The reaction would follow: (i) NO 2 elimination, (ii) nitro-nitrite isomerization, and (iii) a step-wise mechanism involving initial ring opening followed by bond dissociation with a concerted hydrogen shift.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, experiments on these materials are increasing in order to explore important properties such as structural, optical and chemical decomposition mechanisms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Indeed complex crystal structure and high sensitivity to a small external stimuli of these compounds present difficulties in experiments to examine the desired properties such as analysis of the bonding, stability, and studying the polymorphic phases of these materials. On the other hand, theoretical assessment on these materials is an alternative method to provide a description of the structural and electronic properties at various conditions.…”
Section: Introductionmentioning
confidence: 99%